Neuroprotective effect of kaempferol glycosides against brain injury and neuroinflammation by inhibiting the activation of NF-κB and STAT3 in transient focal stroke. - Lu Yu (Public Library of Science (PLoS), 2013)
Background Ischemic brain injury is associated with neuroinflammatory response, which essentially involves glial activation and neutrophil infiltration. Transcription factors nuclear factor-κB (NF-κB) and signal transducer and activator of transcription 3 (STAT3) contribute to ischemic neuroinflammatory processes and secondary brain injury by releasing proinflammatory mediators. Kaempferol-3-O-rutinoside (KRS) and kaempferol-3-O- glucoside (KGS) are primary flavonoids found in Carthamus tinctorius L. Recent studies demonstrated that KRS protected against ischemic brain injury. However, little is known about the underlying mechanisms. Flavonoids have been reported to have antiinflammatory properties. Herein, we explored the effects of KRS and KGS in a transient focal stroke model. Methodology/principal findings Rats were subjected to middle cerebral artery occlusion for 2 hours followed by 22 h reperfusion. An equimolar dose of KRS or KGS was administered i.v. at the beginning of reperfusion. The results showed that KRS or KGS significantly attenuated the neurological deficits, brain infarct volume, and neuron and axon injury, reflected by the upregulation of neuronal nuclear antigen-positive neurons and downregulation of amyloid precursor protein immunoreactivity in the ipsilateral ischemic hemisphere. Moreover, KRS and KGS inhibited the expression of OX-42, glial fibrillary acidic protein, phosphorylated STAT3 and NF-κB p65, and the nuclear content of NF-κB p65. Subsequently, these flavonoids inhibited the expression of tumor necrosis factor α, interleukin 1β, intercellular adhesion molecule 1, matrix metallopeptidase 9, inducible nitric oxide synthase, and myeloperoxidase. Conclusion/significance Our findings suggest that postischemic treatment with KRS or KGS prevents ischemic brain injury and neuroinflammation by inhibition of STAT3 and NF-κB activation and has the therapeutic potential for the neuroinflammation-related diseases, such as ischemic stroke.